HUBUNGAN ANTARA KEYAKINAN TENTANG OBAT DAN KEPATUHAN PENGOBATAN PADA PASIEN OSTEOARTRITIS (Studi di Puskesmas Wilayah Surabaya) - ALWINDA PRISKA YULIMATUSSA’DIYAH, 051411131186 (2018)
The belief about medicines is predicted to be a stronger factor in influencing adherence compared to sociodemographic or clinical factors. The efforts to improve adherence is proven to treath chronic noncommunicable diseases effectively. The medication management therapy of osteoarthritis (OA) is aimed to improve quality of life. This study aimed to see the correlation between beliefs in medicines and medication adherenc in primary health care centers in Surabaya. This study was cross-sectional study using purposive sampling. The Beliefs about Medicines Questionnaire (BMQ) and Adherence to Refills and Medications Scale (ARMS) questionnaire were used in this study to measure the beliefs and adherence respectively. About 57 OA patients of primary health care centers in Surabaya were participated in the study. The results showed that there was a negative correlation between BMQ-Specific Necessity and ARMS scores (p=0,001, r=-0,424). A positive correlation was found in BMQ-General Harm and ARMS scores (p=0,018, r=0,311). This study showed that the belief about medicines an important factor for improving adherence. The total scores for the BMQ-Specific Necessity (16[24-10]), BMQ-Specific Concerns (16[24- 10]), BMQ-General Overuse (12[16-8]), and BMQ-General Harm (11[16- 6]) showed moderate belief about medicines prescribed and about medicines as a whole. The total scores of ARMS (20,98±4,43) showed moderate adherence. To conclude, the belief about medication could be one of the factors that of affecting medication adherence in OA patients at primary health care in Surabaya.